First records of Heterotoma merioptera (Scopoli, 1763) and Aradus serbicus (Horváth, 1888) (Heteroptera: Miridae et Aradidae) from Germany - Morkel, Carsten (Zootaxa, 2010)
The plant bug Heterotoma merioptera (Scopoli, 1763) and the flat bug Aradus serbicus (Horváth, 1888) are recorded for the first time from Germany. Annotations on the circumstances of finding as well as remarks on the species general distribution are given. A. serbicus is considered to represent an ancient, primeval forest relict species within Central Europe; whereas H. merioptera may have some bearing on global warming.